Prevalence of Lymphatic Filariasis based on Morbidity and Healthcare-seeking Practices of Patients in a Gram Panchayat of Paschim Burdwan District, West Bengal - Indranil Saha; Russoti Das; Ajay K. Mandal; Pinki Darlami; Subhajit Datta; Gautam Ghose; Sanjit Dey (Indian Journal of Community Medicine)
Lymphatic filariasis is one of the neglected tropical diseases still present in many areas. A community-based cross-sectional study was conducted during 2019–2020 in the Gourbazar gram panchayat area of Paschim Burdwan District, West Bengal, to find out the prevalence of lymphatic filariasis based on morbidity and its distribution in terms of selected sociodemographic variables and to assess the healthcare-seeking practices of the affected people. The entire area was covered by the National Center for Vector Borne Diseases Control flashcards. Data was analyzed by SPSS software (version 20.0). Overall, the prevalence of LF was found to be 0.97%. About 49.6% of filariasis patients were male. Among the males, the majority suffered from hydrocele, followed by lymphoedema of the legs. Overall, about 2/3rd of the patients (66.1%) consulted with doctors regarding their health problems. Overall, 90.8% consulted from the private healthcare sector and the majority relied on traditional healers. It is now essential to line list the cases and to provide appropriate management from the designated service area so as to promote health and well-being.